Mitochondrial DNA Depletion Syndrome—An Unusual Reason for Interstage Attrition after the Modified Stage 1 Norwood Operation. (20th October 2011) - Cave, Dominic; Ross, David B.; Bahitham, Wesam; Chan, Alicia; Sergi, Consolato; Adatia, Ian
ABSTRACT: We describe a patient with a variant of the hypoplastic left heart syndrome who died 16 weeks after a modified stage 1 Norwood from a mitochondrial DNA depletion syndrome.